2019
DOI: 10.1103/physrevb.99.134510
|View full text |Cite
|
Sign up to set email alerts
|

μSR and magnetometry study of the type-I superconductor BeAu

Abstract: We present muon spin rotation and relaxation (µSR) measurements as well as demagnetising field corrected magnetisation measurements on polycrystalline samples of the noncentrosymmetric superconductor BeAu. From µSR measurements in a transverse field, we determine that BeAu is a type-I superconductor with Hc = 256 Oe, amending the previous understanding of the compound as a type-II superconductor. To account for demagnetising effects in magnetisation measurements, we produce an ellipsoidal sample, for which a d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 61 publications
3
28
0
Order By: Relevance
“…27,28 However, a more comprehensive analysis of the superconducting state in Y 4 Be 33 Pt 16 is currently underway. In particular, because several in-depth muon spin-rotation, relaxation, and resonance experiments performed on another Be-containing non-centrosymmetric superconductor BeAu 24 revealed that not only type-I character, 29 but also a multi-gap nature of superconductivity 30 may exist in such unconventional systems.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 However, a more comprehensive analysis of the superconducting state in Y 4 Be 33 Pt 16 is currently underway. In particular, because several in-depth muon spin-rotation, relaxation, and resonance experiments performed on another Be-containing non-centrosymmetric superconductor BeAu 24 revealed that not only type-I character, 29 but also a multi-gap nature of superconductivity 30 may exist in such unconventional systems.…”
Section: Resultsmentioning
confidence: 99%
“…[47,50], respectively. Note that currently, three sets of C e (T ) and B c (T ) data for BeAu are available in the literature [46][47][48][49][50][51]. Among them, the C e (T ) and B c (T ) dependences from Refs.…”
Section: The Specific Heat and The Thermodynamic Critical Field Of Beaumentioning
confidence: 99%
“…The magnetic field distribution in a type-I superconductor in the intermediate state, which is probed directly by means of TF-µSR, consists of two sharp peaks corresponding to the response of the domains remaining in the Meissner state (B = 0) and in the normal state (B ≡ B c > B ex ). Consequently, the value of B c could be directly and very precisely determined by measuring the position of the B > B ex peak [18,22,[26][27][28][29][30][31][32][35][36][37][38][39][40]. The details of the TF-µSR experiments on elemental Pb and the data analysis procedure are discussed in the Supplemental Material [41].…”
Section: Superconductivity Was First Discovered By Kamerlinghmentioning
confidence: 99%